Optimal risk cut-offs for Down syndrome contingent maternal serum screening. (17th November 2018) - Charoenratana, Cholaros; Wanapirak, Chanane; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Tongsong, Theera
Abstract: Objectives: The objective of this study is to identify the optimal cut-off points of contingent serum screening excluding nuchal translucency (NT) measurement, to categorize the risk level in the first trimester. Methods: A prospective database of women undergoing contingent serum screening, without NT measurement, was reviewed. In conventional categorization, the results of first-trimester screening were categorized into high risk (>1:30) (invasive diagnosis was offered); intermediate risk (1:30–1:1500) (second-trimester screening was needed); and low risk (<1:1500) (no further test). We recategorized the risk levels using various upper and lower cut-offs and compared detection rates, false-positive rates, and rates of intermediate risk. Results: Among 24, 874 women, the prevalence of Down syndrome was 1:691. The previously agreed cut-offs had a detection rate of 88.9% and a false-positive rate of 8.5% with high rate of intermediate risk (38.2%). Re-categorization provided the optimal lower and upper cut-offs 1/900 and 1/50, respectively, giving a detection rate of 86.1%, a false-positive rate of 8.1%, and a rate of intermediate risk of 24.8%. Conclusions: This is the first study on contingent serum screening without NT measurement which shows a high detection rate with an acceptable false-positive rate. The optimal cut-offs to categorize the risk levels of the upper and the lower cut-off was 1:30–1:50 and 1:900, respectively.